2017
DOI: 10.13057/nusbiosci/n090207
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of the extracts and fractions of dahlia tuber (Dahlia variabilis) against pathogenic skin fungi

Abstract: Abstract. Saryono, Octarina N, Yuharmen, Pratiwi NW, Ardhi A. 2017. Antifungal activity of the extracts and fractions of dahlia tuber (Dahlia variabilis) against pathogenic skin fungi. Nusantara Bioscience 9: 146-151. Dahlia plant (Dahlia variabilis) can be easily found in the highlands in Indonesia and its tuber has been reported to have some bioactive compounds which are potential to be utilized as an antimicrobial agent. This study aimed to determine antifungal activity and minimum inhibitory concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Aqueous, ethanol and chloroform extracts of leaves Carica papaya and Psidium guajava leaves also showed antifungal activity against Rhizopus species. One study by 44 suggested that the antimicrobial activity of Acalypha indica leaves extract could be attributed to the active compounds of alkaloids and tannins. According to a study conducted by 45 the presence of bioactive compounds such as alkaloids, tannins, steroids, saponins, flavonoids, glycosides, and phenolic compounds was also detected during it phytochemical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous, ethanol and chloroform extracts of leaves Carica papaya and Psidium guajava leaves also showed antifungal activity against Rhizopus species. One study by 44 suggested that the antimicrobial activity of Acalypha indica leaves extract could be attributed to the active compounds of alkaloids and tannins. According to a study conducted by 45 the presence of bioactive compounds such as alkaloids, tannins, steroids, saponins, flavonoids, glycosides, and phenolic compounds was also detected during it phytochemical testing.…”
Section: Discussionmentioning
confidence: 99%
“…The antipathogenic activity was likely from the effect of phenolic compounds in organic BPE. The phenolic compound inhibited microorganisms by degrading the lipid composition in cell membrane and inhibited the process of membrane biosynthesis causing disruption of cell membrane leading to the decrease in osmosis-barrier ability (Saryono et al, 2017).…”
Section: Antipathogenic Activity Of Organic Bpementioning
confidence: 99%